Efektifitas Sistem Pelayanan Pembuatan Surat Izin Mengemudi (SIM) Secara Online di Satuan Penyelenggara Administrasi (Satpas) Colombo Surabaya - Fatimah, Siti; Radjikan, Radjikan (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
Online SIM is applied for new SIM and SIM renewal. The purpose of this research is to find out and describe the effectiveness of service system of SIM making online in Administrative Administrator Unit (Satpas) Colombo Surabaya; To know and describe the constraints faced in the system of SIM-making services online at the Administrative Administrator Unit (Satpas) Colombo Surabaya; And to know and describe the efforts undertaken to improve the effectiveness of the SIM service making system online at the Administrative Administrator Unit (Satpas) Colombo Surabaya. Analytical technique used is descriptive qualitative. The result of the research shows that the effectiveness of service of making Driver's License (SIM) online at Administrative Administrator Unit (Satpas) Colombo Surabaya is known from several factors, namely: a) Time factor; Indicates that the time required for an online driver's license (SIM) service is 15 to 20 minutes; B) Accuracy factors; Indicates that the staff or parties who provide online driver's license (SIM) service at the Surabaya Provincial Administrative Unit (Satpas) Surabaya have high accuracy and accuracy so that in practice it is rarely found an error in the service process being carried out; And c) Service-style factors; It is known that the style of service providers in this case is the staff or the Administrative Administrator (Satpas) Colombo Colombo as performing the duties and responsibilities of work in accordance with applicable SOP and existing Perkap. The results also indicate that online SIM service at Administrative Administrator Unit (Satpas) Colombo Surabaya is considered effective but not maximal considering there are still some obstacles in the implementation. These constraints consist of: a) there are still people who do not know clearly about the mechanism of the SIM online; B) the number of staff is considered to be lacking; C) there is a network connection or trouble; D) The Administrative Administrator Unit (Satpas) Colombo Surabaya still uses the conventional system in its operational management; And e) at the Surabaya Provincial Administrative Unit (Satpas) Colombo is still under renovation. In relation to the apparent constraints, the efforts made to improve the effectiveness of the SIM-making service system online at the Surabaya Provincial Administrative Unit (Satpas) Surabaya is to conduct socialization through television and radio and socialize with the ball pick-up system; Making additional staff in accordance with the needs, the Parties Satuan Penyelenggara Administrasi (Satpas) Colombo Surabaya can cooperate with the service provider; And updating IT-based infrastructure and training in the use of information technology or Internet-based infrastructure. Keywords: Effectiveness, Service, Driver License (SIM) online